The rise and fall of the medical mediated searcher - ATLAS, M. C (Bulletin of the Medical Library Association, 2000)
The relationship between the development of mediated online literature searching and the recruitment of medical librarians to fill positions as online searchers was investigated. The history of database searching by medical librarians was outlined and a content analysis of thirty-five years of job advertisements in MLA News from 1961 through 1996 was summarized. Advertisements for online searchers were examined to test the hypothesis that the growth of mediated online searching was reflected in the recruitment of librarians to fill positions as mediated online searchers in medical libraries. The advent of end-user searching was also traced to determine how this trend affected the demand for mediated online searching and job availability of online searchers. Job advertisements were analyzed to determine what skills were in demand as end-user searching replaced mediated online searching as the norm in medical libraries. Finally, the trend away from mediated online searching to support of other library services was placed in the context of new roles for medical librarians.